Phosphorus-containing g-C3N4 photocatalysts for hydrogen evolution: A review. (30th December 2022) - Lv, Sijie; Wu, Chunxiao; Ng, Yun Hau; Zhang, Yafei; Peng, Jiahuan; Liu, Yuxi; Zhang, Qichao; Li, Shuang; Sun, Yajie; Jing, Lin; Deng, Jiguang; Dai, Hongxing
Abstract: Graphitic carbon nitride (g-C3 N4 ) is considered a potential photoactive semiconductor for photocatalytic hydrogen evolution (PHE). Although being active in producing hydrogen, it is in general suffering from severe charge recombination rate, low mobility of charge and narrow visible light response range largely, which has restricted its greater application. Existing reviews on g-C3 N4 are lacking of systematic and summative view on the effects of the physical-chemical structure-activity relationship between g-C3 N4 and the modification involving phosphorus (P). Many studies indicate that adding P into g-C3 N4 could effectively elevate the photo-activity. Underlying reasons for the observed improved photo-activity are discussed in this review. Here, P-containing g-C3 N4 photocatalysts are grouped into the categories of P elemental doping, composite with elemental P, as well as the addition of metal phosphide as cocatalysts. These P-containing g-C3 N4 possess novel properties demonstrating favorable photocatalytic activities as compared with the other elemental (such as O, S, B)-based materials. Therefore, in this mini review, we summarize and discuss the advances on the P-containing g-C3 N4 photocatalysts, including the preparation strategies, physicochemical properties, the application for hydrogen production as well as the related reaction mechanism. Importantly, the physical-chemical structure-activity relationship between g-C3 N4 and the integrated P is revealed. Finally, an overview of the current research status and challenges on future is presented, which would be helpful in designing and developing other P-containing photocatalysts for various photocatalytic applications. Graphical abstract: Image 1 Highlights: Current progress of P containing g-C3 N4 photocatalysts for H2 production. Preparation and basic physicochemical properties of P containing g-C3 N4 . The role of P in P containing g-C3 N4 for photocatalysis. Photocatalytic activity and related mechanism of P containing g-C3 N4 .